The Montessori Experiment in Rhode Island (1913-1940): Tracing Theory to Implementation over Twenty-Five Years - Susan Zoll (University of Kansas, 2017)
This article highlights archived documents pertaining to a 25-year experimental classroom implemented by Clara Craig, then supervisor of training at the Rhode Island Normal School. Craig is notable as she was the only participant in the first International Montessori Training Course in Rome, Italy, in 1913, to gain approval from the Rhode Island Board of Education to study the Montessori Method. Her administrative position at the Rhode Island Normal School provided her with a rare opportunity to influence both teacher preparation and classroom curriculum upon her return. The article traces implementation of the Montessori Method and its Americanized revision, serving as one of the earliest longitudinal examples (1913-1940) of a state-sanctioned Montessori classroom, well beyond the acknowledged first-wave era (1911-1917). Craig's experience provides a historical perspective that can inform current Montessori initiatives working within complex education and policy contexts.